Gender Discrimination in the Novel Renjana by El Alicia (Forum Ilmu Sosial, 2022)
Literary work is a creation of creative work. One of the functions of literature is as a medium to manifest human life through language. In other words, literature is a reflection of society. Gender inequality has always been an interesting issue because patriarchal culture is still deeply rooted in the Indonesian community. The superiority and domination of men over women are also frequently mentioned and criticized through works of fiction and non-fiction found in films and novels. Especially in books both explicitly and implicitly allude to and review gender issues, as in El Alicia's Renjana novel. This research is a type of qualitative research. This research analyzes gender discrimination in the book Renjana by El Alicia. The analytical method used is discourse analysis from Sara Mills. The result shows that gender discrimination appears in El Alicia's Renjana novel. Including stereotypes, marginalization, violence, and subordination. Explicitly, the definition of stereotypes against women as voiceless creatures whose often opinions ignored in several quotes in the novel. The marginalization of women's illustration shows in the rules that bind the Gentala character as the main character. Meanwhile, the manifestation of violence against women is the domination of male characters who show superiority and power over women, as in one of the scenes of violence that Bestari experienced when he refused to serve Sang Wiyasa. Subordination with women shows in this novel, where often women's voices are ignored in discussions.